'Half-cut' science: a qualitative examination of alcohol industry actors' use of peer-reviewed evidence in policy submissions on Minimum Unit Pricing. (1st February 2019) - Cullen, Dana; Smith, Katherine; Collin, Jeff
Abstract : Aim: To assess the extent to which alcohol industry actors cited evidence in submissions to the Scottish Parliament Health and Sport Committee's 2011 call for written evidence on the Alcohol (Minimum Pricing) (Scotland) Bill and to compare any citations of peer-reviewed evidence to original sources. Methods: All submissions to the consultation (n=128) were manually searched to identify those written by alcohol industry actors (n=25). The reference lists of all the alcohol industry submissions were reviewed and peer-reviewed sources were retrieved, read and assessed against their in-text citation within the alcohol industry submissions. Results: Although most industry submissions cited evidence of some sort, only 7 (28%) cited peer-reviewed evidence. Comparing the total number of citations to peer-reviewed evidence (n=17) to original sources demonstrates that 82% were questionably cited. Conclusion: Our findings demonstrate that the majority of references to peer-reviewed evidence in this sample of alcohol industry policy submissions were misleading with examples of citations being presented as supportive of arguments that the original evidence source specifically argued against. This suggests that even the depiction of peer-reviewed evidence within alcohol industry policy submissions needs to be treated with caution.